The Effect of Anesthesia Type During Delivery on Neonatal Otoacoustic Emission Hearing Test Results: A Tertiary Center Experience - Yakıştıran, Betül; Karslı, Mehmet; Canpolat, Emre; Oğuz, Yüksel; Altınboğa, Orhan; Celen, Sevki (Zeitschrift für Geburtshilfe und Neonatologie, 2020)
Background Hearing is essential for the healthy development of an infant as language is one of the main stimulants of intellectual capacity. We investigate the effect of anesthesia type during delivery on neonatal otoacoustic emission (OAE) hearing test results.Methods This retrospective cross-sectional study includes 1,493 healthy, full-term (39/0–40/6 gestational weeks) newborns of healthy women and who were delivered by cesarean section. Newborns were divided into 2 groups based on their anesthesia type during delivery: 1) general anesthesia group (n=160), and 2) spinal anesthesia group (n=1333). Maternal age, anesthesia type, birth weight, gestational age at birth, neonatal gender, 1st–5th minute APGAR scores, and OAE results were compared between the groups.Results 1287 (86.2%) newborns were reported to have passed the first step of OAE; 206 (13.8%) newborns were reported to have failed the first step and passed the second test. In the general anesthesia group, 133 (83.1%) of the newborns passed the first OAE test and 27 (16.9%) newborns had false-positive results. In the spinal anesthesia group, 1,154 (86.6%) of the newborns passed the first OAE test and 179 (13.4%) newborns had false-positive results. The difference between the 2 groups by false-positive values was found to be statistically significant (p<0.001).Conclusions Type of delivery anesthesia may have an effect on the false-positive rates of OAE test results.
Keywords: hearing screening; otoacoustic emissions; caesarean delivery; anesthesia